Association among vocabulary size, academic achievement, English language proficiency, and language dominance - Rahman, Arifur (2017)
Vocabulary is acknowledged as a key to Second Language (L2) proficiency (Coady, 1997) and previous studies suggest that learners of English as a Second Language (ESL) need a vocabulary size of 9000-word families to comprehend academic texts at tertiary level (Nation, 2007). Earlier studies also showed that a significant positive correlation exists between learners’ vocabulary size and academic achievement. In previous studies on ESL learners' vocabulary knowledge, different variables have been found to be related to bilingual learners’ inadequate vocabulary size. As the 2nd year Malay ESL learners of the current study are bilinguals, it is hypothesized that their dual language profile can provide evidence of their language dominance, which may be related to their overall vocabulary size. Therefore, this study measured Malay ESL learners’ vocabulary size and language dominance at tertiary level and the relationship between vocabulary size, academic achievement, language proficiency, and language dominance, and the extent to which variance in academic achievement can be explained by these factors. Ninety-six students from four undergraduate programmes offered at University Putra Malaysia were recruited using stratified sampling technique and their vocabulary size and language dominance were measured using two sets of questionnaires. The 20,000 Vocabulary Size Test (Version A) was used to measure receptive vocabulary size, and the Bilingual Language Profile (BLP) was used to measure language dominance. The learners’ Cumulative Grade Point Average (CGPA) and the Malaysian University English Test (MUET) scores were obtained from their academic transcripts. Data were analyzed using descriptive statistics, correlation analysis, and multiple regression analysis. The results show that 92% of the participants studied in the present study have a vocabulary size beyond 9,000 word families. A moderate and positive association was found between receptive vocabulary size and English language proficiency, language dominance and academic achievement. Receptive vocabulary size was found to be the only predictor of academic performance when compared with other variables such as language proficiency, and language dominance. The study shows that on average Malay ESL learners at tertiary level have knowledge of about 11,268-word families of vocabulary. Although the result showed that vocabulary size, language proficiency, and language dominance have a significant association with academic achievement, vocabulary size is the only significant contributor to academic achievement, and it is predicted to contribute as much as 25% towards academic achievement. The findings indicate value in fostering frequent vocabulary testing at tertiary level in order to support learners with inadequate vocabulary sizes. The use of VST in this study proved to be useful for helping lecturers to determine the kind of attention they should pay to vocabulary for particular groups of learners. Moreover, the findings suggest that the VST maybe a reliable and cost-effective post enrolment screening tool of tertiary level learners in ESL settings. This understanding of Malay ESL tertiary learners’ receptive vocabulary knowledge can help language planning and policy maker in designing appropriate syllabus, language courses, and offer operational strategies to enhance vocabulary knowledge so that the learners can do well in their tertiary level studies.